Artista que fingere: a manipulação da imagem entre a imanência, as sobrevivências e a dupla-dobra - Marina Romagnoli Bethonico (2015)
This research has as its theme the study of my artistic process andproduction jointly with concepts tangential to it, constituting a practical and theoretical work that has as a proposition to make the making, think about the making, think about the thinking, make the thinking. A reflection is conducted about method in the visual arts, dialoguing with the philosopher Gilles Deleuze and his plane of immanence.From then on, the processes of two individual exhibitions held in the period of the master's degree are analysed, articulating notions of image-multiplicity, figure, fingere and double-fold. The artistic influence of Giotto di Bondone and Fra Angelico is discussed, exploring the concepts of fascination and survival of the image, having Georges Didi-Huberman as a main theoretical reference.The artist is considered as a practitioner of the fingere, from the moment that he manipulates materials, images and concepts to produce reality. The creative process defined and justified the practical/theoretical research method and, from the concepts presented but not dependent on them , the image is considered as an underlying potency to the theme in general.